Ethanolic Extract of Marsdenia condurango Ameliorates Benzo[a]pyrene-induced Lung Cancer of Rats: Condurango Ameliorates BaP-induced Lung Cancer in Rats - Sikdar, Sourav (J Pharmacopuncture, 2014)
OBJECTIVES: Condurango is widely used in various systems of complementary and alternative medicines (CAM) against oesophageal and stomach ailments including certain types of cancer. However, until now no systematic study has been conducted to verify its efficacy and dose with proper experimental support. Therefore, we examined if ethanolic extract of Condurango could ameliorate benzo[a]pyrene (BaP)-induced lung cancer in rats, in vivo to validate its use as traditional medicine. METHODS: Fifteen male and 15 female Sprague-Dawley (SD) rats were treated with 0.28 mg/kg of Sweet Bee Venom (SBV) (high-dosage group) and the same numbers of male and female SD rats were treated with 0.2 mL/kg of normal saline (control group) for 13 weeks. We selected five male and five female SD rats from the high-dosage group and the same numbers of male and female SD rats from the control group, and we observed these rats for four weeks. We conducted body-weight measurements, ophthalmic examinations, urinalyses and hematology, biochemistry, histology tests. RESULTS: A histological study revealed gradual progress in lung tissue-repair activity in Condurango-fed cancer-bearing rats, showing gradual tissue recovery after three months of drug administration. Condurango has the capacity to generate reactive oxygen species (ROS), which may contribute to a reduction in anti-oxidative activity and to an induction of oxidative stress-mediated cancer cell-death. Condurango-activated pro-apoptotic genes (Bax, caspase-3, caspase-9, p53, cytochrome-c, apaf-1, ICAD and PARP) and down-regulated antiapoptotic-Bcl-2 expression were noted both at mRNA and protein levels. Studies on caspase-3 activation and PARP cleavage by western blot analysis revealed that Condurango induced apoptosis through a caspase-3-dependent pathway. CONCLUSION: The anticancer efficacy of an ethanolic extract of Condurango for treating BaP-induced lung cancer in rats lends support for its use in various traditional systems of medicine.